Impact of Physical Parameters on Dosing Errors due to a Syringe Exchange in Multi-Infusion Therapy - Snijder Roland A.; Konings Maurits K.; van den Hoogen Agnes; Timmerman Annemoon M.D.E (De Gruyter, 2017)
Infusion therapy is challenging and dosing errors may occur due to physical phenomena related to the infusion hardware, despite the use of accurate syringe pumps. These errors typically occur after interventions, such as the exchange of a syringe. We aimed to characterize and quantify dosing errors due to a syringe exchange in relation to physical properties of infusion hardware.